The Development of iManage-PC, an Online Symptom Monitoring and Self-management Tool for Men With Clinically Localized Prostate Cancer. Issue 1 (January 2022) - Murphy, Karly M.; Sauer, Christina; Yang, Dershung; Hass, Niina; Novakovic, Kristian; Helfand, Brian; Nadler, Robert; Schalet, Benjamin D.; Victorson, David
Abstract : Background: Prostate cancer (PC) often impacts 4 major aspects of health-related quality of life (HRQL): urinary, sexual, and bowel dysfunction, and anxiety. Online tools may be helpful in supporting the development of self-management skills that can improve HRQL. Objective: The aim of this study was to develop and pilot-test an online symptom monitoring and self-management program, iManage-PC. Methods: A literature search, input from experts, and feedback from patients were used to develop iManage-PC. A 4-week, single-arm pilot study was conducted with 96 men with prostate cancer. We evaluated system usability, acceptance, and satisfaction and examined preliminary effects on patient-reported outcomes. Results: Rates of retention (94.8%) and adherence to symptom monitoring (95.0%-97.0%) were high. Most participants rated the tool as satisfactory and acceptable (81.2%-94.3%). Related-samples Wilcoxon signed rank tests revealed that participants reported increased self-efficacy related to their ability to manage their adverse effects ( T = 1772.0, P < .001, r = 0.39), physical discomfort ( T = 1259.0, P < .001, r = 0.40), and stress and worry ( T = 1108.5, P = .001, r = 0.34). Global mental and physical health also improved ( T = 1322.0, P = .032, r = 0.23, and T = 1409.0, P = .001, r = 0.35, respectively). Conclusions: Future research with such tools should examine the potential role of cut-score–derived management interventions to improve engagement, symptom management self-efficacy, and HRQL. Implications for Practice: Our findings are consistent with a growing body of literature that supports the feasibility and acceptability of remotely delivered interventions.